2021
DOI: 10.1111/irv.12918
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations of COVID‐19 differ by age and obesity status

Abstract: Background Age and obesity status are associated with severe outcomes among hospitalized individuals with COVID‐19. It remains unclear whether age and obesity are risk factors for milder COVID‐19 illness. Methods We prospectively enrolled SARS‐CoV‐2‐exposed individuals. Participants recorded symptoms for 28 days and were tested for SARS‐CoV‐2 by reverse transcription polymerase chain reaction (RT‐PCR) and serology. Type, number, and duration of symptoms and SARS‐CoV‐2 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 25 publications
(39 reference statements)
2
7
0
3
Order By: Relevance
“…Symptoms such as fever, cough, headache, and odynophagia with sudden onset of symptoms and attack on the general state were primarily reported in this Mexican population; such symptoms are in agreement with those previously reported by Rajakapse et al [28]. Similar to previous reports, underlying conditions such as asthma and obesity were also associated with severe COVID-19 in Mexican children admitted to HIMFG [8,25,29,30]. In contrast to other studies, in which fever, cough, tachypnea, general malaise, nasal congestion, rhinorrhea, refusal to feed/difficulty feeding, and diarrhea were reported as the most common symptoms, we observed that the children and adolescents without comorbidities had rhinorrhea and polypnea as the major symptoms [31].…”
Section: Discussionsupporting
confidence: 91%
“…Symptoms such as fever, cough, headache, and odynophagia with sudden onset of symptoms and attack on the general state were primarily reported in this Mexican population; such symptoms are in agreement with those previously reported by Rajakapse et al [28]. Similar to previous reports, underlying conditions such as asthma and obesity were also associated with severe COVID-19 in Mexican children admitted to HIMFG [8,25,29,30]. In contrast to other studies, in which fever, cough, tachypnea, general malaise, nasal congestion, rhinorrhea, refusal to feed/difficulty feeding, and diarrhea were reported as the most common symptoms, we observed that the children and adolescents without comorbidities had rhinorrhea and polypnea as the major symptoms [31].…”
Section: Discussionsupporting
confidence: 91%
“…Vitamin D levels have been found to be significantly different in those with or without taste loss in COVID-19 [55]. Regarding BMI, the duration of taste loss did not significantly differ between overweight/obese and normal weight participants, although those with higher BMI did appear to have a greater frequency of taste loss but not smell loss [56]. Sex is perhaps the most widely studied variable in associated with sensory disruption.…”
Section: Differences Between Prolonged and Rapid Taste Recoverymentioning
confidence: 96%
“…Essas alterações fisiológicas supracitadas resultantes da obesidade podem explicar os achados encontrados nos Estados Unidos, onde os indivíduos com sobrepeso ou obesidade, comparados às pessoas com peso dentro da normalidade, apresentaram mais sintomas, especialmente, os sintomas respiratórios que incluíam tosse e falta de ar (17) .…”
Section: Discussionunclassified
“…Em relação à frequência dos sintomas, duração e níveis de gravidade autorrelatados por adolescentes obesos e com sobrepeso foram semelhantes aos de adultos. Os adolescentes apresentaram mais sintomas com maior gravidade autorreferida que durou mais tempo do que as crianças menores de 12 anos (17) . Esse achado pode ser um indicativo de ausência de sintomas ou sintomatologia branda em crianças menores e que podem não ser associados à infecção por SARS--CoV-2, o que pode dificultar o diagnóstico e resultar em subnotificação nesse grupo da população.…”
Section: Discussionunclassified